Barriers and enablers to diabetic eye screening attendance: An interview study with young adults with type 1 diabetes. Issue 3 (29th December 2021) - Prothero, Louise; Lawrenson, John G.; Cartwright, Martin; Crosby‐Nwaobi, Roxanne; Burr, Jennifer M.; Gardner, Philip; Anderson, John; Presseau, Justin; Ivers, Noah; Grimshaw, Jeremy M.; Lorencatto, Fabiana; ,
Abstract: Aim: The aim of this study was to identify barriers and enablers of diabetic eye screening (DES) attendance amongst young adults with diabetes living in the United Kingdom. Methods: Semistructured qualitative interviews with adults aged 18–34 years with diabetes. Participants were purposively sampled to aim for representation across gender, geographical locations, diabetes type, years since diabetes diagnosis and patterns of attendance (i.e. regular attenders, occasional non‐attenders, regular non‐attenders). Data were collected and analysed using the Theoretical Domains Framework (TDF) to explore potential individual, sociocultural and environmental influences on attendance. Data were analysed using a combined deductive and inductive thematic analysis approach. Barriers/enablers were mapped to behaviour change techniques (BCTs) to identify potential strategies to increase attendance. Results: Key barriers to attendance reported by the sample of 29 study participants with type 1 diabetes, fell within the TDF domains: [ Knowledge ] (e.g. not understanding reasons for attending DES or treatments available if diabetic retinopathy is detected), [ Social Influences ] (e.g. lack of support following DES results), [ Social role and Identity ] (e.g. not knowing other people their age with diabetes, feeling 'isolated' and being reluctant to disclose their diabetes) and [ Environmental Context and Resources ] (e.g. lack of appointment flexibility and options for rescheduling). Enablers included: [ Social Influences ] (e.g. support of family/diabetes team), [ Goals ] (e.g. DES regarded as 'high priority'). Many of the reported barriers/enablers were consistent across groups. Potential BCTs to support attendance include Instructions on how to perform the behaviour ; Information about health consequences ; Social support (practical) and Social comparison . Conclusions: Attendance to diabetic eye screening in young adults is influenced by a complex set of interacting factors. Identification of potentially modifiable target behaviours provides a basis for designing more effective, tailored interventions to help young adults regularly attend eye screening and prevent avoidable vision loss.